3D printing of carbon-based materials: A review. (15th October 2021) - Blyweert, P.; Nicolas, V.; Fierro, V.; Celzard, A.
Abstract: Unlike conventional subtractive methods, 3D printing allows rapid prototyping and customization on demand. However, as a process recently applied to carbon-based materials, 3D printing faces many challenges, including the precise tailoring of the printed material and the control of its porosity, as well as obtaining directly printed (pure) carbon. The present review focuses on the latest advances in carbonaceous materials in 3D printing to address these challenges. A brief introduction to additive manufacturing processes is given, followed by a summary and many recent examples of manufacturing processes, structural characteristics, and applications of various carbon-based composites and carbonaceous materials. Finally, viewpoints and prospects for this emerging field are presented. Graphical abstract: Image 1